Sensors, Medical Images and Signal Processing: - Depeursinge, A.; Müller, H.; Section Editors for the IMIA Yearbook Section on Sensor, Signal, and Imaging Informatics (Yearbook of Medical Informatics, 2010)
Objectives To summarize current excellent research in the field of medical sensor, signal and imaging informatics.Method: Synopsis of the articles selected for the IMIA (International Medical Informatics Association) Yearbook 2010.Results: Current research in the field of sensor, signal, and imaging informatics is characterized by theoretically sound techniques and evaluations with focus in imaging informatics.Conclusions: The best paper selection of articles on sensors, signal, and imaging informatics shows examples of excellent research on methods concerning theoretically sound original development in this field. Research published in 2009 was characterized by the emergence of mature computerized diagnosis aid frameworks with assessment of input and output quality. The purpose of these systems is clearly to bring new image and signal interpretation tools to clinicians.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; image processing; signal processing; medical sensors